Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi, Sosialisasi, dan Penerapan Akuntansi Terhadap Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM - Mutiari, Kadek Neti; Yudantara, Agus Pertama (Universitas Pendidikan Ganesha, 2021)
This research was conducted with the aim of knowing the effect of education level, understanding of accounting, socialization, and application of accounting on the preparation of MSME financial reports based on SAK-EMKM. The data used in this research is primary data where primary data is collected through questionnaires and the measurement technique used is the Likert scale technique. This research was conducted in Buleleng Regency. The population in this study were all small business actors in Buleleng Regency, where the number of small business actors in Buleleng Regency was 947 MSMEs. The sample was selected by purposive sampling technique, the number of samples was 210 small business actors. The data analysis technique consisted of data quality test, descriptive analysis, classical assumption test, multiple linear regression analysis, t test, and determination coefficient test (R2) with the help of SPSS version 21.0 for windows. Based on the research results, it shows that each variable level of education, understanding of accounting, socialization, and application of accounting has a positive effect on the preparation of financial statements based on SAK-EMKM (Y). This means that all of the variables used can influence MSME actors in preparing financial reports based on SAK-EMKM.